Alfredo Ellis Junior e o separatismo de São Paulo como alternativa ao Varguismo - Forte, Paulo (2017)
This search Alfredo Ellis Junior e o Separatismo de São Paulo como alternativa ao varguismo by Paulo Forte, the main aim of this research is the relation between the ideas of nation, separatism and the “paulista” prominence in the Alfredo Ellis Junior’s work. As an organic intellectual of the agro exporting class fraction, he try to justify in a historical deterministic approach the paulista separatism using the paulista’s original myth. The ex-deputy favoured a paulista nation ideology using racialist concepts, in vogue at the brazilian first republic, given a scientific look to racial supremacy ideology that opposes paulistas and brazilians. His goal was create an alternative state against the Vargas government, concerned with the interests of the agro exporting class fraction. After the defeat in the 1932 Civil War, he favoured another political project: reorganize Brazil in a sui generis confederation. In our research, we’ve use mainly the Lúcio Flávio Rodrigues de Almeida studies about national ideology and also the studies of Nicos Poulantzas about state and production relations in a Bourgues State